Pharmacological treatment of negative symptoms in schizophrenia: update and proposal of a clinical algorithm - Cerveri, Giancarlo (Neuropsychiatr Dis Treat, 2019)
The clinical presentation of schizophrenia encompasses symptoms divided into three dimensions: positive, negative, and cognitive. Negative symptoms (NS), in particular, have a major impact on the quality of life of the affected subject, and, differing from positive symptoms, are often associated with a limited response to pharmacotherapy. To date, studies specifically investigating NS in schizophrenia are scant; therefore, proper selection of therapy for NS remains a major unmet medical need. Given the heterogeneity of the clinical presentation of schizophrenia, the treatment of NS, as well as therapy for other associated symptoms, should be largely individualized according to a patient’s specific characteristics. In this paper, we review current knowledge on NS and construct a clinical algorithm for the treatment of schizophrenic conditions with pronounced NS. Overall, data from the literature suggest that second-generation antipsychotics, such as cariprazine and amisulpride, should be preferred over first-generation antipsychotics (FGAs), as they are associated with better functional outcomes and lower cognitive impairment. The combination of antipsychotics and antidepressants may also improve NS while addressing some affective disorders associated with schizophrenia; however, no clear information is available on the effects of this combination on primary NS or on the mechanism of action of the combination. In the proposed clinical algorithm, we suggest that cariprazine should be used as first-line treatment for patients with predominant NS, and that amisulpride should be considered as an alternative in cases of cariprazine failure. Further treatment lines may include the use of olanzapine and quetiapine, and add-on therapy with antidepressants.